Cross-border energy trade with Laos : perceived benefits, policy participation, and the impacts on local livelihoods in Nong Khai, Thailand - Worrawoot Jumlongnark; Tsusaka, Takuji W.; Thi, Phuoc Lai Nguyen; Vilas Nitivattananon; Pramanik, Malay; Royal Thai Government Fellowship; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Cross-border energy trade has been extensively researched; yet its impacts on local communities remain unclear. Likewise, Thailand{u2019}s cross-border electricity trade with Laos significantly boosts the economic progress; yet research is scarce on its livelihood impacts on residents of the Mekong River basin. This dissertation investigated the characteristics and policy process of Thailand{u2019}s electricity trade with Laos, and assessed its effects on local livelihood outcomes based on the Sustainable Livelihoods Framework in the border area of Mueang District of Nong Khai Province. Utilizing a mixed-method approach, the study employed a questionnaire survey with 339 residents, key informant interviews with community leaders and local traders, and document analysis. The quantitative analysis included inferential statistics such as the t-test, ANOVA, Spearman correlation, and the ordinary least squares, while qualitative analysis used thematic analysis and content analysis. Key findings are: (1) Thailand{u2019}s current cross-border energy trade with Laos is aligned with the New Trade Theory; (2) The process of facilitating this trade is characterized by a policy community; yet, stakeholder participation is limited, with an uneven distribution of power and interests. The policy process resembles a policy community rather than a policy issue; (3) The levels of livelihood outcomes were neutral, with the 2creation of working days3 exhibiting the lowest average score (2.81 on the scale of 1 to 5), while 2well-being and capabilities3 displayed the highest average score (4.09); household participation in cross-border electricity trade policy positively influenced the livelihood outcomes. The livelihood outcomes were also affected by community-level characteristics. These findings can guide governments in raising awareness of cross-border electricity trade policies and promoting sustainable local livelihoods. Recommendations include boosting public awareness, maximizing local benefits, and enhancing participation in policymaking. Future research should focus on rural areas to address livelihood challenges and identify potential policy gaps comprehensively.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Development and Sustainability
Thesis (Ph.D.) - Asian Institute of Technology, 2024
Keywords: Laos -- Commerce -- Thailand; Thailand -- Commerce -- Laos; Energy policy -- Laos; Energy policy -- Thailand